A Study on the Customer Insight towards Advertising Practices in HDFC Standard Life Insurance Company Limited - D Rajasekar (International Journal of Supply Chain Management, 2018)
About products and services and how to it is being used, obtained the main purpose of advertisement is to inform potential customers. Through creation and reinforcement of brand image and loyalty in order to increase the consumption of goods and services many advertisements are designed. For both factual information and persuasive messages this being the main purpose of the advertisement. Likes of television, radio, movies, magazines, newspapers, video games, internet, and billboard all these mediums advertise messages. On behalf of the company the advertising agencies places advertisements. Various places like on the seats of grocery carts, on the walls of an airport walkway, on the sides of buses, heard in telephone hold messages and in-store public address systems the advertisements can be seen. For selling a product, service to the general public which includes political parties interest groups, organizations that supports religion, new recruits from military the organizations spend large amount of money on advertisement but do not strictly sell. Some rely purely on free channels, public service announcements, and non profit organizations for advertising clients.